Establishment of a network for the public atmospheric air monitoring and informing the population - Holik, Yuriy; Maksiuta, Nataliia (Technology audit and production reserves, 2020)
Perelik prohramnykh produktiv v haluzi okhorony atmosfernoho povitria. Available at: https://menr.gov.ua/content/perelik-programnih-produktiv-v-galuzi-ohoroni-atmosfernogo-povitrya.html The object of research is monitoring the state of atmospheric air pollution in agglomerations with subsequent informing the population. Monitoring the state of the city's atmospheric air is of great importance both at the state level and for the public. In this work, public monitoring of atmospheric air is created on the example of the city of Poltava (Ukraine). The creation of a network for public monitoring of the state of air pollution in the city provides for independent monitoring of air pollution, based on decrees and other guidelines on air quality. In accordance with the existing requirements, the state monitoring of atmospheric air has a number of disadvantages, namely: – lack of monitoring of suspended solids, including PM2.5 and PM10; – monitoring of atmospheric air pollution at stationary observation posts is carried out a maximum of 4 times a day; – lack of a system of informing the population about the state of the air in the city, in particular, PM2.5 and PM10 pollution – lack of automated systems for analyzing air quality, that is, monitoring is carried out by sampling. In contrast to the conduct of state observation, public monitoring will provide not only informing the population, involving them in monitoring, but will also increase environmental awareness, responsibility, and create an additional tool for controlling air pollution. For the effective functioning of the public monitoring network, rules have been developed for conducting public monitoring of the state of atmospheric air pollution in the city with a description of the location of pollution sensors, their operation and basic requirements. Also, a website has been developed based on the monitoring database, reflecting the results of public monitoring. Taking into account that if the database contains data on the indicators of installed sensors (point measurements), then the site for informing the population is a visualization of the control results throughout the city, that is, it will act as a model for the distribution of pollution in the city's atmospheric air.